UJI AKTIVITAS DAYA INGAT EKSTRAK DAUN CENGKEH (Syzygium aromaticum) TERHADAP MENCIT PUTIH (MUS MUSCULUS) DENGAN METODE RADIAL ARM MAZE - Putri, Fera Adila; Ardiyantoro, Bagas; Lutfiyanti, Niken (JIFI (Jurnal Ilmiah Farmasi Imelda), 2025)
Memory loss is often associated with dementia, which can be caused by oxidative stress and increased free radicals. Therefore, this study aims to determine the activity of clove leaf extract (Syzygium aromaticum) in improving memory in white mice (Mus musculus) and to determine the most effective dose. In the practice that has been carried out, it has been proven that clove leaves containing flavonoid compounds are extracted using the maserai method with 70% ethanol solvent. The test used was the Radial Arm Maze in five groups, namely negative control, positive control, and test group with a dose of clove leaf extract of 50 mg/kgBW, 100 mg/kgBW, and 200 mh/kgBW. This study involved three stages, namely, acclimatization, 10% alcohol induction, and treatment according to group. It can be concluded that the results of the statistical test showed a significant increase in the memory of mice in all dose treatments compared to the negative control. The most effective dose was 200 mg/kgBW, with a decrease in latency time of 92.4 seconds and an error rate of 2.63%.